Insect Pests of Fast Growing Tree Species-II. Effect of Various Fumigants on Poplar Stem Borer, Apriona cinerea Chevrolet (Lamudae) in New Forest Plantations - Chatterjee, P. N.; Singh, Pratap; Prasad, Ganga (Indian Forester, 1969)
no abstract